Les Déterminants Des Conflits De Compétences Dans Le Processus De Décentralisation En Cote d’Ivoire - Jean-Arsene, Guiriobe Paumahoulou (European Scientific Journal, ESJ, 2016)
This study identifies and analyses the factors that determine jurisdictional conflicts prevailing in the decentralization process in Côte d’Ivoire. To achieve these objectives, we interviewed, using semi-structured interviews, resource persons in the departments of Alépé, Grand-Bassam, Guiglo and the District of Abidjan. From these interviews, it appears that conflicts of jurisdiction are classified into two categories: vertical conflicts and horizontal conflicts. The vertical conflicts arise between central structures of Government and local authorities. Horizontal conflicts occur between local authorities. Usually caused by structural realities, these conflicts are fueled and poisoned by economic and especially political factors.